A new species of chameleon (Squamata: Chamaeleonidae) from the Aberdare Mountains in the central highlands of Kenya - Stipala, Jan; Lutzmann, Nicola; Malonza, Patrick K.; Wilkinson, Paul; Godley, Brendan; Nyamache, Joash; Evans, Matthew R. (Zootaxa, 2012)
We describe a new species of chameleon, Trioceros kinangopensis sp. nov., from Kinangop Peak in the Aberdare moun-tains, central highlands of Kenya. The proposed new species is morphologically and genetically distinct from other mem-ber of the bitaeniatus-group. It is morphologically most similar to T. schubotzi but differs in the lack of sexual sizedimorphism, smaller-sized females, smoother, less angular canthus rostrales, smaller scales on the temporal region and abright orange gular crest in males. Mitochondrial DNA indicates that the proposed new taxon is a distinct lineage that isclosely related to T. nyirit and T. schubotzi. The distribution of T. kinangopensis sp. nov. appears to be restricted to the afroalpine zone in vicintiy of Kinangop Peak and fires may pose a serious threat to the long-term survival of this species.